Reflection of the Content of Sensitive Education of Junior Pupils in the Curriculum for Primary Classes of Gymnasiums for Men in Ukraine in the Early Twentieth Century - Chorna, Viktoria (Pedagogical Discourse, 2011)
The results of analyses of the curriculum for preparatory and primary classes of gymnasiums for men in Ukraine, according to different educational subjects with the aim to determine their resources for perceptive development of the pupils are shown.